A whole biodiesel conversion process combining isolation, cultivation and in situ supercritical methanol transesterification of native microalgae. (August 2015) - Jazzar, Souhir; Quesada-Medina, Joaquín; Olivares-Carrillo, Pilar; Marzouki, Mohamed Néjib; Acién-Fernández, Francisco Gabriel; Fernández-Sevilla, José María; Molina-Grima, Emilio; Smaali, Issam
Graphical abstract: Highlights: Resistant microalgae isolated from South Mediterranean lagoons were studied. Microalgae were successfully cultivated in batch and continuous photobioreactors. Photosynthetic performance and nutrient removal efficiency were investigated. A high biodiesel yield was obtained by in situ supercritical treatment of wet algae. All transesterifiable lipids can be converted to biodiesel by supercritical process. Abstract: A coupled process combining microalgae production with direct supercritical biodiesel conversion using a reduced number of operating steps is proposed in this work. Two newly isolated native microalgae strains, identified as Chlorella sp. and Nannochloris sp., were cultivated in both batch and continuous modes. Maximum productivities were achieved during continuous cultures with 318 mg/l day and 256 mg/l day for Chlorella sp. and Nannochloris sp., respectively. Microalgae were further characterized by determining their photosynthetic performance and nutrient removal efficiency. Biodiesel was produced by catalyst-free in situ supercritical methanol transesterification of wet unwashed algal biomass (75 wt.% of moisture). Maximum biodiesel yields of 45.62 wt.% and 21.79 wt.% were reached for Chlorella sp. and Nannochloris sp., respectively. The analysis of polyunsaturated fatty acids of Chlorella sp. showed a decrease in their proportion when comparing conventional and supercritical transesterification processes (from 37.4% to 13.9%, respectively), thus improving the quality of the biodiesel.